Changes in swim performance and perceived stress, and Recovery in female collegiate swimmers across a competitive season - Nagle, J. A.; McMillan, J. L.; Munkasy, B. A.; Joyner, A. B.; Roorda, A.; Scott, M. K.; Rossi, S. J. (Journal of Swimming Research, 2015)
Optimal sport performance involves balancing the accumulation of training stress with adequate recovery (Budgett, 2000; Hollander & Meyers, 1995). Continuous evaluation of an athlete's performance levels, stress levels, and recovery states during a competitive season is important in determining an athlete's readiness for competition. Limited examination of these three factors appears for collegiate athletes; thus this study's purpose was to examine effects of training load on psychological and performance variables among collegiate female athletes across a competitive season. Nineteen NCAA Division I female swimmers completed monthly testing including six tethered swim tests and seven Recovery-Stress Questionnaires (RESTQ-76), yielding mean force (Fmean) and Total Recovery-Stress Score (TRSS). Individual session Rated Perceived Exertion scales (RPE) were used to categorize participants into Training Load Groups (TLG). Analysis revealed no significant interaction between TLG, and either TRSS or Fmean. There were significant time effects on Fmean (p=0.004): between T1 and T2 (p=0.004), and T3 and T4 (p=0.01). There were significant changes in meters completed with differences between T1 and T2 (p<.001), between T4 and T5 (p<.001), and between T5 and T6 (p<.001). TRSS and meters completed had an inverse relationship where an increase in meters occurred concurrently with decreases in TRSS and vice versa. This study's results indicate that, while there was no difference between groups for performance, perceived stress, and recovery, there were significant changes across a season that could have practical implications for athletes, coaches, and researchers.